Acute Left Branch Block in Pregnancy: A Case of Peripartum Cardiomyopathy - Mesut Alçı; Emre Uysal (Düzce Tıp Fakültesi Dergisi)
Peripartum cardiomyopathy is a rare but significant condition occurring during late pregnancy or early postpartum period. Risk factors of peripartum cardiomyopathy include pregnancy, advanced maternal age, multiple pregnancies, and preeclampsia. This case report presented a case of a 32-year-old woman who developed an acute left bundle branch block due to peripartum cardiomyopathy during pregnancy. This case underscores the importance of considering peripartum cardiomyopathy in pregnant patients presenting with cardiac symptoms, especially those with risk factors such as advanced maternal age and multiple pregnancies. Prompt diagnosis and management are crucial to mitigate maternal and fetal risks associated with peripartum cardiomyopathy. Preeclampsia can lead to the development of peripartum cardiomyopathy, a rare but severe condition. Accurate diagnosis and appropriate treatment are essential. Clinicians should consider peripartum cardiomyopathy in patients presenting with preeclampsia symptoms.